Three-dimensional displacement and slip distribution of the 2021 Mw 7.4 Maduo (Tibetan Plateau) earthquake determined by GNSS and InSAR - Wu, Wenqiang; Zhang, Yongzhi; Hao, Xiaoye; Liu, Jiaojiao (Journal of Asian earth sciences, 2024)
•The seismogenic fault is a typical sinistral strike-slip fault with a rupture length of over 160 km.•The displacement in E-W is the biggest among three-dimensional displacements with the RMSE 3.01 mm.•The peak slip is 5.53 m with the seismic moment of Mw 7.3 in the homogenous half-space model.•The peak slip is 5.96 m with the seismic moment of Mw 7.4 in the layered half-space model. On May 22, 2021, an Mw 7.4 earthquake occurred on the Maduo-Jiangcuo fault, located in Maduo County, Qinghai Province (China). According to the co-seismic deformation and the three-dimensional displacement reached from the interferometric synthetic aperture radar (InSAR) and the global navigation satellite system (GNSS), the rupture trace in the NWW direction was mapped, spanning a length of approximately 160 km and the earthquake happened on a typical sinistral strike-slip fault. In three-dimensional displacement, the displacement in E-W was bigger than that in N-S and vertical, with the RMSE 3.01 mm, 15.28 mm, and 5.16 mm respectively. Moreover, the slip distribution inverted with the homogeneous half-space model and layered half-space model, indicated that the corresponding magnitude was 7.3 Mw and 7.4 Mw, and the corresponding peak slip was 5.53 m and 5.96 m. The correlation coefficients of observed and predicted both exceeded 0.791, meeting the need for slip inversion. What is more, the peak inversion depth was no more than 15 km with strike angle and dip angle of 269° and 82.9° in the homogeneous half-space model and 265° and 83.7° in the layered half-space model, respectively. In addition, the Coulomb stress changes decreased on the Maduo-Jiangcuo fault and accumulated on the East Kunlun fault, which might cause aftershocks and future earthquakes were still possible. In short, the 2021 Mw7.4 Maduo earthquake made it possible to unravel seismic behavior in the Tibet plateau, which is of great significance for seismic hazard research.